2015
DOI: 10.11648/j.ajbls.s.2015030201.12
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry of Genus Polygonatum: A Review

Abstract: Abstract:The current review article deals with the comprehensive phytochemical background of genus Polygonatum. It was observed that out of approximately 60 species, only 9 are subject to phytochemical studies that led mostly to the isolation of saponins, phytohormones, glycosides, flavonoids, esters and alkaloids. However, the remaining species are still waiting for exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In a research by Deng et al [21], the results showed saponin, flavonoid and sugar in the rhizomes of P. odorata. These findings matched with a review report by Khan and Rauf [22], who concluded that homoisolflavanone, triterpenoids and steroidal saponins could be extracted from the rhizomes of P. odorata. Other than that, other chemical constituents reported by the previous study are also shown in (Table 1).…”
Section: Phytochemical Analysis Of Persicaria Odoratasupporting
confidence: 90%
“…In a research by Deng et al [21], the results showed saponin, flavonoid and sugar in the rhizomes of P. odorata. These findings matched with a review report by Khan and Rauf [22], who concluded that homoisolflavanone, triterpenoids and steroidal saponins could be extracted from the rhizomes of P. odorata. Other than that, other chemical constituents reported by the previous study are also shown in (Table 1).…”
Section: Phytochemical Analysis Of Persicaria Odoratasupporting
confidence: 90%
“…Khan and Khatoon, (2008) have reported that the local people in northern Pakistan use P. geminiflorum for the treatment of uterine tumor, menstrual abnormalities, gout, and skin diseases. Moreover, Khan and Rauf, (2015) have comprehensively described the phytochemical constituents of different species in the genus, and the associated antimibacterial, antifungal and antioxidant activities. This study has also reported that P. geminiflorum is rich in phenolics, saponins, alkaloides and phytoharmones, and therefore is a high value medicinal plant, like the most commonly explored P. vericillatum.…”
Section: Introductionmentioning
confidence: 99%